The Membrane-Bound Aspartyl Protease BACE1: Molecular and Functional Properties in Alzheimer’s Disease and Beyond - Dislich, Bastian; Lichtenthaler, Stefan F. (Frontiers in Physiology, 2012)
The β-site APP cleaving enzyme 1 (BACE1) is a transmembrane aspartyl protease involved in Alzheimer’s disease (AD) pathogenesis and in myelination. BACE1 initiates the generation of the pathogenic amyloid β-peptide, which makes BACE1 a major drug target for AD. BACE1 also cleaves and activates neuregulin 1, thereby contributing to postnatal myelination, in particular in the peripheral nervous system. Additional proteins are also cleaved by BACE1, but less is known about the physiological consequences of their cleavage. Recently, new phenotypes were described in BACE1-deficient mice. Although it remains unclear through which BACE1 substrates they are mediated, the phenotypes suggest a versatile role of this protease for diverse physiological processes. This review summarizes the enzymatic and cellular properties of BACE1 as well as its regulation by lipids, by transcriptional and by translational mechanisms. The main focus will be on the recent progress in understanding BACE1 function and its implication for potential mechanism-based side effects upon therapeutic inhibition.